Metode Pengajaran Nahwu dalam Perspektif Pemikiran Az-Zarnuji Dan Ibnu Khaldun: Sebuah Studi Analisis Komparatif Dalam Kitab Ta'lim Al-Muta'allim Dan Muqaddimah - Abdullah Asyiq; Rifky Rosian An Nur (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
The teaching of nahwu (Arabic grammar) often faces pedagogical challenges rooted in rigid instructional approaches, lack of contextualization, and insufficient integration of cognitive and ethical dimensions in the learning process. This article aims to explore and compare the educational philosophies of two prominent classical Islamic scholars, Az-Zarnuji in Ta'lim al-Muta'allim and Ibn Khaldun in Muqaddimah, in order to formulate a more humanistic, integrative, and relevant conceptual framework for nahwu instruction within contemporary education. Employing a conceptual paper approach, this study utilizes qualitative content analysis and a comparative strategy based on primary and secondary textual sources. The analysis reveals that Az-Zarnuji emphasizes the ethical foundations of learning, including intention, discipline, and spiritual teacher–student relationships, while Ibn Khaldun highlights sociological perspectives, gradual learning stages, and the function of language within social structures. Synthesizing these two perspectives results in a pedagogical model of nahwu that balances character formation with linguistic competence in a contextualized manner. The article’s primary contribution lies in reconstructing classical Islamic educational thought as a foundation for developing Arabic grammar teaching methods that are academically effective and morally transformative. The study opens pathways for curriculum design and instructional strategies in nahwu education that are more adaptive, participatory, and philosophically grounded within the modern Islamic education framework.